Livelihood strategies and diversification amongst the poor: Evidence from South African household surveys - Syden Mishi; Zintle Sikhunyana; Nomasomi Ngonyama; Kin Sibanda (The Journal for Transdisciplinary Research in Southern Africa, 2020)
South Africa faces persistent challenges of poverty, unemployment and inequality. Recently, there has been growing literature trying to effectively address such challenges as the livelihood strategies of the poor need to be adequately understood. This article studied the livelihood strategies and diversification among the poor in South Africa using two data sets, namely the Statistics South Africa General Household Survey 2016 (GHS) and the Programme to Support Pro-poor Policy Development (PSPPD II)-University of Fort Hare (UFH) Economics survey. The study measured welfare using per capita income standardised by the adult equivalence scale (AES) which accounts for intra-household variations in members’ access to household’s resources and therefore corrects for economies of scale. Logistic regression techniques were employed to test the stated hypotheses. The GHS 2016-based results are in line with the sustainable livelihood framework, which posits that households need access to different sets of assets to sustain livelihoods. In this context, access to different assets has been shown to increase the probability of engaging in high-value strategies that will ensure sustainability of livelihoods. The PSPPD-UFH Economics data collaborate GHS-based results, showing that assets’ access deprivation increases the odds of relying on non-labour income (like social grants) than engaging in high-value strategy (no farming income). Male-headed households and those with greater access to financial capital are more diversified.